On the Cutting Edge: Tales of a Cold War Engineer at the Dawn of the Nuclear, Guided Missile, Computer and Space Ages - Murdock, Scott D (Air & space power journal, 2011)
Readers learn that Brodsky had a hand in improving the aerodynamic stability of atomic bombs, solving guidance and control problems on Navy missiles, and designing satellites and a moon rover, among other accomplishments.